Edukasi Cuci Tangan Pakai Sabun (Ctps) Sebagai Upaya Pencegahan Tranmisi Penyakit Dalam Keluarga Di Desa Mesjid Bungie - Nurlela Mufida; iklima; Azhar Mu'alim; Idawati; Ismuntania (Lebah, 2023)
Washing your hands with soap and running water can clean your hands of dirt and germs. Dirt and germs can cause various diseases, such as diarrhea, upper respiratory tract infections, avian influenza, hepatitis A, worms, skin and eye diseases. The aim of this activity is to increase family knowledge about the importance of washing hands with soap as an effort to prevent disease transmission so that there is a change in attitudes towards clean and healthy living behavior. The target of this service is families who have family members with a history of infectious diseases in the last 3 months. This service provides health education about handwashing with soap as an effort to prevent disease transmission in the family. It is hoped that the implementation of this education can improve healthy living behavior in families and understand the prevention of disease in family members as an effective preventive measure to reduce the risk of disease transmission